Questions to the requirement to equate “illicit origin” with “generic criminal injustice” in the Plenary Cassation Judgment No. 1-2017 - Guzmán Fiestas, Rudy Santiago (2024)
The objective of this contribution is to determine if in all cases prior criminal activity should be equated with unfair, as established in foundation 19 of Plenary Cassation Judgment No. 1-2017. It is proposed that such equalization be required as soon as the criminal activity is discovered, but not for cases in which it has not been. In the latter case, its accreditation is possible through the circumstantial evidence method, excluding other possible illegal origins other than criminal.